Becoming Platformized Teacher in Digital Age : The Representation of English Teacher Identity in Merdeka Mengajar - Yuli Ika Lestari; Johny Alfian Khusyairi (English Language and Literature International Conference (ELLiC) Proceedings, 2023)
Platform Merdeka Mengajar  (PMM)  is an official  platform issued by Indonesian Ministry of Education and Culture  to  ensure teachers face the changes in the post-pandemic educational situation successfully. The use of PMM  facilitates teachers to teach according to their students' abilities, provides training to improve teacher’s competence, and  engages the community to  build teaching collaborative ecosystem with colleagues. The study discusses the identities represented on Merdeka Mengajar as  official platform to support teacher in implementation of  Merdeka Curriculum. It focuses on the extent to which features available in PMM as Platform provided by government, which correspond to fundamental components of pedagogies. The objectives of the research are : (1) explore the strategies of forming English teacher identities in the  Merdeka Mengajar , and (2) analyse  the offered identities as English Teacher  represented of contents  by using pedagogical  perspective. Qualitative method of the study gathered the data by observing the content of Platform Merdeka Mengajar  including; inspirational videos, self-training, proof of my work, student assessment and teaching devices. The first findings indicates that the identities as English Teacher  formed by (1) providing ideal identities, (2) supporting the needs of teacher, (3) appreciating teacher participation, and (4) involving larger audiences  (colleagues).  The identity of English Teacher represented into the use of (1) purposive diction of the content, (2) various resources, and (3) the interaction of teacher as content maker- audience in the platform. Those can be indicated as the new form of  English teacher identity not only as social identity but also digital identity.